Sustainable cultural heritage management : a case study in Sarawak, Malaysia - Nur Auni, Ugong (Emerald Publishing Limited, 2024)
Purpose – The purpose of this study is to provide the challenges and sustainability of Sarawak’s cultural heritage and archaeotourism. Design/methodology/approach – The research method practiced is a qualitative descriptive approach using primary, secondary and field research sources. Findings – The study found that the challenges faced by cultural heritage in Sarawak are the need for human resource expertise, research funding, documentation and reporting, aesthetic value and loss of sites, standard research procedures, bureaucratic processes, vandalism, natural threats, collection management and urbanization and modernization. Therefore, the proposed resolution to address the stated challenges is uniformity and professionalism, archaeotourism and public engagement. Research limitations/implications – The sample size for this study may be limited due to the nature of the case study. The findings may not reflect the perspectives of all stakeholders involved in cultural heritage management in Sarawak. Future studies could use larger sample sizes to capture a more diverse range of perspectives. Practical implications – The practical implications of this study provide valuable insights for stakeholders involved in cultural heritage management, including government agencies, NGOs and local communities. By incorporating the findings into their practices, stakeholders can promote sustainable cultural heritage management and contribute to sustainable development. Social implications – The social implications of this study highlight the potential for cultural heritage management to contribute to social and economic development, community empowerment and the preservation of cultural identity and diversity. By incorporating the findings into their practices, stakeholders can promote inclusive and sustainable cultural heritage management practices that benefit local communities and contribute to the broader social and cultural fabric of society. Originality/value – The originality and value of this study lie in its detailed and nuanced case study approach, interdisciplinary perspective, emphasis on sustainability and community involvement and practical recommendations for improving cultural heritage management practices.